2005
DOI: 10.1007/s00535-004-1518-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of decreased nitrite production by bezafibrate in patients with primary biliary cirrhosis

Abstract: This study reconfirms the therapeutic efficacy of bezafibrate in patients with PBC, including those with UDCA-resistant PBC. Downregulation of nitrite production by DCs may have some relationship with the therapeutic efficacy of bezafibrate; however, further study will be needed to clarify whether or not the antiinflammatory activity of bezafibrate is mediated through nitrite production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The therapeutic efficacy of bezafibrate, a hypolipidemic drug, has been shown in patients with PBC in some pilot studies. Down-regulation of nitrite production by dendritic cells may have some relationship with the therapeutic efficacy of bezafibrate for PBC (24). In our study, we found that bezafibrate could reduce BAFF-stimulated B-cell-induced Treg cell apoptosis and promote TGF-β and IL-10 expression in Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic efficacy of bezafibrate, a hypolipidemic drug, has been shown in patients with PBC in some pilot studies. Down-regulation of nitrite production by dendritic cells may have some relationship with the therapeutic efficacy of bezafibrate for PBC (24). In our study, we found that bezafibrate could reduce BAFF-stimulated B-cell-induced Treg cell apoptosis and promote TGF-β and IL-10 expression in Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of small clinical studies have assessed the potential efficacy of fibrates in PBC [47-72] (Table 1). Firstly, in 1999 Iwasaki et al reported a significant improvement in the biochemical profile and disease symptoms after adding bezafibrate in PBC that were non-responders to UDCA.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that the combination therapy of UDCA and bezafibrate significantly improved liver function early in 1 month. 21 Combination therapy reduced the serum levels of gamma-glutamyltransferase, ALP, and immunoglobulin M, but there were no significant differences in the incidence of all-cause mortality, adverse events, and pruritus. 12 , 22 However, none of the studies elucidated the long-term prognosis, efficacy, and safety of combination therapy.…”
Section: Discussionmentioning
confidence: 91%
“… 24 , 25 It has been proposed that bezafibrate plays a therapeutic role by downregulation of nitrite production by dendritic cells. 21 One study evaluated changes in the serum cytokine levels in response to treatment to identify the cytokines that reflect improved clinical results. Serum interleukin-18 (IL-18) levels in the groups at two time points were measured before (baseline) assignment of either treatment and after 12 months of the assigned treatment, but no significant difference was observed between the two groups.…”
Section: Discussionmentioning
confidence: 99%